2017
DOI: 10.1007/s10067-017-3904-2
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes and risk factors of early readmission in patients with intestinal Behçet’s disease

Abstract: Hospital readmission rate is an integral quality of care measurement for hospitalized patients which is unknown for intestinal Behçet's disease cases. The purpose of this study was to investigate the risk factors and outcomes for patients readmitted early with intestinal Behçet's disease. We retrospectively reviewed patients with intestinal Behçet's disease who were readmitted to our hospital between 2005 and 2016. We then analyzed the risk factors and outcomes for early readmission within 3 months. Of the 204… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…Our intestinal ABD patients with poor outcomes (non-healing intestinal ulcers) accounted for 34.86%, slightly lower than the rate of 58.3% reported in other studies of intestinal ABD patients [10, 13, 18]; no patients died during follow-up. Previously, the identified independent risk factors for poor prognosis in intestinal ABD were male gender, mucosal healing, volcano-shaped ulcers, larger size of intestinal ulcers (> 2 cm) and elevated CRP levels (≥ 44 mg/L )[10, 2022].…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Our intestinal ABD patients with poor outcomes (non-healing intestinal ulcers) accounted for 34.86%, slightly lower than the rate of 58.3% reported in other studies of intestinal ABD patients [10, 13, 18]; no patients died during follow-up. Previously, the identified independent risk factors for poor prognosis in intestinal ABD were male gender, mucosal healing, volcano-shaped ulcers, larger size of intestinal ulcers (> 2 cm) and elevated CRP levels (≥ 44 mg/L )[10, 2022].…”
Section: Discussioncontrasting
confidence: 66%
“…We also speculate that early onset of ABD (< 7 years) is an important factor related to the occurrence of adverse events (relapse or non-healing intestinal ulcers) in our intestinal ABD patients. Some authors found that early-onset intestinal ABD patients presented with more severe clinical symptoms and poorer clinical outcomes because of stronger immune responses and higher frequency of volcano-shaped ulcers, also significantly associated with recurrences and poor prognosis in intestinal ABD [18, 34].…”
Section: Discussionmentioning
confidence: 99%
“…1,29 In patients with active Behçet's disease, the frequencies of Th17 cells were remarkably increased in peripheral circulation and elevated IL-17 levels were observed in sera. 37,38 Recently, DMI has been reported to inhibit Th17 cell differentiation from naive splenocytes. 20 However, little is known about the role of DMI in regulating antigen-specific Th17 cell Here, we found that DMI-treated mice displayed a significantly reduced frequency of Th17 cells and downregulated IL-17 production, as well as dramatically decreased expression of pathogenic Th17 signature genes such as Il17a, Il17f, Il23r, Il1r1, Csf2, Ccl5, and Cxcr3, suggesting the possible inhibitory role of DMI in antigenspecific Th17 responses.…”
Section: Discussionmentioning
confidence: 99%